Fowl Adenovirus Serotype 4 SD0828 Infections Causes High Mortality Rate and Cytokine Levels in Specific Pathogen-Free Chickens Compared to Ducks - Li, Rong; Li, Gen; Lin, Jing; Han, Shaojie; Hou, Xiaolan; Weng, Hongyu; Guo, Mengjiao; Lu, Zhong; Li, Ning; Shang, Yingli; Chai, Tongjie; Wei, Liangmeng (Frontiers in Immunology, 2018)
Hydropericardium syndrome and inclusion body hepatitis, together called hydropericardium-hepatitis syndrome, are acute infectious diseases found in chickens. These diseases are caused primarily by fowl adenovirus serotype 4 (FAdV-4) strains. In this study, we isolated a FAdV-4 strain (SD0828) from clinically diseased chickens and phylogenetically analyzed the L1 loops of the hexon protein sequences in 3-week-old specific-pathogen-free chickens and ducks infected intramuscularly and orally, determining differences in the pathogenicity by observing clinical signs and gross and histological lesions. We also detected the viral load in tissue samples. Post-infection necropsy showed that all chickens but no ducks exhibited typical necropsy lesions. Additionally, all chickens infected intramuscularly died within 2 days post-infection (dpi), and all those infected orally died within 5 dpi, whereas no infected ducks died before 28 dpi. Quantitative real-time polymerase chain reaction analysis was used to determine the viral load in the tissues of hearts, livers, spleens, lungs, and kidneys and in cloacal cotton swabs from infected chickens and ducks at 1, 2, 3, 5, 7, 14, 21, and 28 dpi. The greatest number of viral DNA copies was found in the livers of infected chickens, yet no virus was found in any samples from infected ducks. In addition, the viral load increased over time in both chicken and duck embryo fibroblasts (CEFs and DEFs, respectively); in the former, replication speed was significantly greater than in the latter. Innate immune responses were also studied, both in vivo and in vitro. In CEFs, DEFs, and chickens infected intramuscularly, but not in infected ducks, mRNA expression levels of proinflammatory cytokines (interleukin-6 and -8) and interferon-stimulated genes (Mx and OAS) were significantly up-regulated. Although some cytokines showed significant up-regulation in the orally-infected chickens, most did not change significantly. Finally, the duck retinoic acid-inducible gene I and its caspase activation and recruitment domain both had significant antiviral functions in CEFs, particularly after 24 hours post-infection. Taken together, this research provides new insights into the interactions between FAdV-4 and the innate immune systems of studied hosts (chickens and ducks).